Surgical catastrophic health expenditure at New Somerset Hospital, a South African public sector hospital - Naidu, Priyanka (University of Cape Town, 2021)
Background: Catastrophic health expenditure (CHE) and impoverishing health expenditure (IHE) are significant barriers to surgical care. Worldwide, 3.7 billion people risk financial catastrophe if they require surgery, mostly affecting the poorest populations in LMICs. Surgical CHE and IHE are not described in the South African context. The objectives of this study were: 1) to determine the proportion of surgical participants at New Somerset Hospital (NSH) ), a second-level public sector South African hospital, who experienced CHE and IHE and 2) to determine the risk factors associated with out-of-pocket (OOP) payments. Methods: This study used a cross-sectional retrospective questionnaire administered to participants admitted to any department of surgery (obstetrics, gynaecology, general surgery, urology, otorhinolaryngology, or orthopaedics) for a surgical procedure at NSH. Direct healthcare expenditure for the surgical admission was defined to be catastrophic according to three definitions: 1) OOP payments 10% or more of annual household expenditure (HHE) (CHE10); 2) OOP payments 25% or more of annual HHE (CHE25); 3) OOP payments 40% or more of capacity to pay (CHE40). IHE was based on the national poverty lines and was defined according to new impoverishment or worsening impoverishment, as a result of OOP expenditure on the surgical admission. Multivariate regression analysis was used to assess the relationship between OOP payments and per capita HHE, age, type of procedure, department to which participant was admitted, distance from NSH, and length of stay. Results: Out of the 274 participants interviewed: 263 were included in the analysis (4% attrition rate). Two (0.8%), five (1.9%), and three (1.1%) participants experienced CHE according to the CHE40, CHE10, and CHE25 definitions, respectively. About 98.5% of participants spent less than 10% of their annual HHE, while 95.4% spent less than 10% of their annual non-food expenditure OOP. Median OOP expenditure was R100 (IQR R15 – R350). About 23% of the participants (n=62) were not charged for their surgical admission. Low per capita HHE (p=0.02), cancer (p=0.001), having a non-generous health insurance plan (p=0.002), and the hospital bill amount (p<0.001) correlated positively with OOP expenditure on healthcare. Linear regression revealed that there was no correlation between the proportion of OOP payments and LOS or distance. One in five patients (n=50, 19%) experienced new or worsening impoverishment and were pushed below the poverty line for receiving surgical care at a public hospital. Furthermore, 65 (25%) patients reported their household was unable to cope or household still recovering from the financial burden of the surgical admission. Discussion: Surgical CHE was not common among this study population, however IHE was substantial and the majority of participants incurred OOP for surgical care, with the main drivers of OOP costs being the hospital bill and transport. Financial catastrophe might have been low because: 1) most participants were protected by the uniform patient fee schedule and therefore did not incur a medical bill and 2) direct non-medical costs did not account for a significant proportion of OOP payments. Understanding the financial impacts of OOP health care expenditure is essential in the planning of the impending National Health Insurance in South Africa.